Ready Player One - Cline, Ernest; Mendelsohn, Ben; 1993-; Sheridan, Tye; 1996-; Cooke, Olivia; 1946-; Spielberg, Steven (Burbank, CA, 2018)
When the creator of a virtual reality world called the OASIS dies, he releases a video in which he challenges all OASIS users to find an Easter egg which will give the finder his fortune.
Keywords: Cline, Ernest; Film adaptations; Drama; Dystopias; Drama; Wealth; Drama; Easter eggs (Computer programs); Drama; Virtual reality; Feature films; Film adaptations; Action and adventure films; Video recordings for people with visual disabilities; Science fiction films